RETRACTED ARTICLE: Tiliroside as a CAXII inhibitor suppresses liver cancer development and modulates E2Fs/Caspase-3 axis - Rui Han; Hongxing Yang; Lingeng Lu; Lizhu Lin (Scientific Reports)
Abstract Liver cancer is the fatal cause of cancer deaths worldwide due to its aggressiveness and lack of effective therapies. Tiliroside (C30H26O13) is an active compound extracted from herb plant Tribulus terrestris L., which has been used as alternative therapy in clinic practice. However, its therapeutic use against liver cancer has not been previously reported. Here, we showed that Tiliroside exerted significantly higher anti-proliferation effect on liver cancer cell lines Hep3B and SNU-449 than on liver normal cell THLE-3 cells or NC group, respectively, by using MTS assay. Results from colony formation, immigration and invasion assays support the anticancer efficacy of Tiliroside and its low-toxic property while treating liver normal cell THLE-3. 3D spheroid formation and CD133 expression level also displays its anti-stemness effect. It has been showed that Tiliroside may function as Carbonic anhydrases XII (CAXII) inhibitor and affects apoptotic E2F1/E2F3/Caspase-3 axis by using CAXII esterase activity assay, Human carbonic anhydrase 12 (CA-12) ELISA Kit, quantitative reverse transcription PCR (RT-qPCR) as well as CaspACE Assay System, respectively. In summary, we demonstrate for the first time that Tiliroside suppresses liver cancer development possibly by acting as a novel CAXII inhibitor, which warrant further investigation on its therapeutic implications.